DISKURSUS MAKNA TOLERANSI TERHADAP NON-MUSLIM DALAM MUHAMMADIYAH SEBAGAI GERAKAN ISLAM BERKEMAJUAN (ANALISIS HERMENEUTIKA PAUL RICOEUR) - romadlan, said (Universitas Muhammadiyah Surakarta, 2019)
This study focus on the process of understanding how Muhammadiyah is interpreted as Islamic organisation abaout tolerance toward non-muslim. The understanding about tolerance toward non-muslim is important because, there are discrimination, intimidation, and attack toward minority groups. Furthermore, this tolerance problems can caused or as trigger to radical actions, especially if it related to political leadership issue. This study aims to understand how the process of understanding of Muhammadiyah as Islamic movement organization about tolerance toward non-muslim. This study used hermeneutika Paul Ricoeur methodology which emphasis on the interpretation on distantiation between text and reader. The findings mentioned that the understanding about tolerance toward non-muslim is rely in al-Qur'an's al-Hujurat verse 15